Antidiabetic Activity of Laligurans (Rhododendron arboreum Sm.) Flower - Bhandary, Megh Raj; Kawabata, Jun (Journal of Food Science and Technology Nepal, 2009)
Anti-diabetic activity was examined in Laligurans (Rhododendron arboreum Sm) flower and active compounds were isolated from it. Aqueous methanolic extract of the flower of Laligurans was found to show inhibitory activity on the rat intestinal ?-glucosidase. Both the water-soluble and ethyl acetate-soluble portions from the aqueous methanolic extract showed inhibitory activities on ?-glucosidase, demonstrating higher activity by the ethyl acetate-soluble portion. From the ethyl acetate-soluble portion, ?-glucosidase inhibitor quercetin-3-O-?-D-galactopyranoside (hyperin) was isolated through enzyme-assay guided separation. The isolated compound showed a dose dependent ?-glucosidase inhibitory activity with IC50 values of 1.66 mM and 0.76 mM for sucrase and maltase, respectively. This study revealed that Laligurans flower contains antidiabetic potential which property might be helpful to develop medicinal preparations, nutraceutical or functional food for diabetes and its complications. Key words: Laligurans; Rhododendron arboreum; Medicinal herb; a-Glucosidase inhibitor; Diabetes; Nepal Journal of Food Science and Technology Nepal Vol. 4, September, 2008, Page: 61-63